The impact of psychological factors on hypertension and its psychological intervention in pilot selection candidates - Dou, Xue-ting; Ji, Ming-jing; Sun, Zhong-yang; Sun, Hong-liang; Wang, Yuan; Zou, Hai-bin; Wang, Si-yang; Gong, Lin (Frontiers in Psychology, 2025)
BackgroundIndividual blood pressure levels can be influenced by psychological factors.ObjectiveThis study aimed to investigate the relationship between hypertension and psychological states, as well as the underlying mechanisms, using a combination of cross-sectional comparison and experimental intervention.MethodsA total of 102 individuals with hypertension and 108 individuals with normal blood pressure participating in pilot selection were recruited. Individuals with hypertension were divided into two intervention groups and a control group: one group received relaxation therapy alone, while the other received a combination of relaxation therapy and cognitive training. Questionnaires were administered to assess anxiety levels and perceived stress.ResultsThe results showed a significant positive correlation between perceived stress and blood pressure in the BBG, and a marginal positive correlation between anxiety and blood pressure. No such correlations were found in the normal blood pressure group. Pre- and post-intervention analyses indicated that the intervention group exhibited a significant reduction in blood pressure compared to baseline levels, along with a notably higher retest pass rate. However, anxiety levels increased significantly across all groups.ConclusionThese findings suggest that blood pressure is influenced by anxiety and perceived stress, and psychological interventions can effectively manage blood pressure. However, these interventions may not primarily operate through reducing anxiety, and further research is needed to explore the psychological mechanisms involved.